Bentuk Tanggung Jawab Negara dalam Memberikan Perlindungan Hukum Bagi Warga Negara yang Terlibat Terorisme Di Negara Lain - Maria Febronia Tawurutubun; Lucia Charlota Octovina Tahamata; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Each citizen protection right is in itself reciprocated with the state's obligation to fulfill it. The role of countries is urgently needed and even compulsory to protect, advance and fulfill the rights of citizens. The government's responsibility to protect the country is not only in Indonesia but also abroad and Indonesian citizens who are involved in terrorism in other countries.Purposes of the Research: The purpose of this writing is knowing of state responsibilities under the protection of citizens involved in terrorism in other countries.Methods of the Research: The writing method used in the research isa normative-law study using three approaches of legislation, a conceptual approach and a case approach aimed at both assessing and knowing about how a country's responsibility is protected by citizens who are involved in terrorism in other countries by international law.Results of the Research: Countries that provide protection to citizens involved in terrorism in other countries are a form of national responsibility based on international laws and a number of laws that apply in Indonesia. The law enforcement agency has been providing legal assistance through the mechanism of the applicant.